2007
DOI: 10.1016/j.jconrel.2007.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Glioma selectivity of magnetically targeted nanoparticles: A role of abnormal tumor hydrodynamics

Abstract: Magnetic targeting is a promising strategy for achieving localized drug delivery. Application of this strategy to treat brain tumors, however, is complicated by their deep intracranial location, since magnetic field density cannot be focused at a distance from an externally applied magnet. This study intended to examine whether, with magnetic targeting, pathological alteration in brain tumor flow dynamics could be of value in discriminating the diseased site from healthy brain. To address this question, the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 29 publications
(38 reference statements)
3
63
0
Order By: Relevance
“…However, it has been shown that the tumor's vascular structure is significantly different in gliomas and is characterized by increased permeability. 26 Conjugation of SPIONs with EGF increased the retention of particles in the tumor; thus, we observed a dramatic accumulation of SPION-EGF conjugates throughout the glioma (Figure 9). The MR detectable accumulation of these conjugates started to appear 24 hours after IV injection, and it further increased after 48 hours.…”
Section: Discussionmentioning
confidence: 73%
“…However, it has been shown that the tumor's vascular structure is significantly different in gliomas and is characterized by increased permeability. 26 Conjugation of SPIONs with EGF increased the retention of particles in the tumor; thus, we observed a dramatic accumulation of SPION-EGF conjugates throughout the glioma (Figure 9). The MR detectable accumulation of these conjugates started to appear 24 hours after IV injection, and it further increased after 48 hours.…”
Section: Discussionmentioning
confidence: 73%
“…Magnetic nanoparticles (MNPs) have intrinsic magnetic properties that enable their use as contrast agents in MRI (8,11). Because MNPs are also sensitive to external magnetic forces, magnetic targeting (MT) actively enhances their deposition at the target site, increasing the therapeutic dose delivered beyond that obtainable by passive diffusion (12).…”
mentioning
confidence: 99%
“…In the present study and in (9), 9L gliosarcomas presented higher mean and median BV than their contralateral part while Hoechst staining of 9L showed that not all the smaller vessels were perfused. Other immunohistochemical staining studies (23,24) showed that 9L tumors were less perfused with a smaller vascular density relative to their contralateral part suggesting a lower BV. A potential answer to these differences may be given by the segmented histogram analysis showing that only the 0-1% and over 6% BV categories were increased relative to the contralateral side in 9L.…”
Section: Discussionmentioning
confidence: 93%
“…To qualify and validate the different angiogenic phenotype inferred from the MRI data, correlations with quantitative immunohistochemical data as in (8) will be needed in the future. However, there is already an abundant literature reporting quantitative parameters such as vascular density and perfusion parameters derived from immunohistochemical staining in C6, 9L (9,23,24) and human glioblastomas (13). Most studies demonstrated strong correlations between quantitative VSI MRI parameters and histopathological data (7,9,(25)(26)(27) in various tumor types.…”
Section: Discussionmentioning
confidence: 99%